Corporate Tax Disclosure in Indonesia: Trends, Content, and Determinants Based on GRI Standard 207 - Aulia, Sandra (UI Scholars Hub, 2024)
This study analyzes the trends, content, and factors influencing corporate tax disclosure in Indonesia based on GRI Standard 207. Data were obtained from sustainability reports of companies listed on the Indonesia Stock Exchange for 2021–2023 and analyzed using content analysis, descriptive methods, and panel data regression. The findings show a significant increase in tax disclosure in line with GRI Standard 207 from 2021 to 2023. The financial and energy sectors had the highest disclosure rates, while the technology and property sectors had lower adoption. The